Survival analysis of patients with sepsis in Brazil - Eliane Pereira da Silva; Vinícius da Costa Duarte; Miguel Maia Soares; Alexia Tayane Menezes de Melo; Emily Ramos Calife; Gilmar da Silva Rebouças; Dyego Leandro Bezerra de Souza (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: This study aimed to analyze the survival of septic patients and to assess prognostic factors. METHODS: Patients with sepsis, severe sepsis, and septic shock were followed up and clinical and laboratory data were collected. The sepsis-related organ failure assessment (SOFA) score was calculated. RESULTS: The overall 30-day survival rates of patients with sepsis, severe sepsis, and septic shock were 86.3%, 72.5%, and 20%, respectively. Mortality was related to old age, septic shock, coagulopathy, lactate level, and high SOFA score among other factors. CONCLUSIONS: Identification of prognostic variables may reduce sepsis-related mortality.